A report on the practice in industry training in fish preservation. - Feliciano, Minviluz C. (Diliman College of Fisheries, University of the Philippines, 1965)
A campaign towards expanding our knowledge and adopting the most effective means of preserving and utilizing our fishery products has been in progress for many years. In lone with this, the college of fisheries of the University of the Philippines has been training students and providing them with modern trends and practical skills in this field. Upon completion of two years academic training in fish preservation and upon fulfillment of all the requirements therein, students undergo a four-month practice-in-industry, a period which enables them to apply the principles they learned in the classrooms. This report on smoking, sinaeng and canning (only boiled tuna is discussed) as major topics and shrimp kroepek as minor topic, was prepared carefully that it might be of help to everybody. I believed that there are shortcomings but I hope this study will lead to the improvement of these Important fishery commodities. Any suggestions, criticisms or corrections from readers will be profoundly appreciated.
Practicum Report (Undergraduate, Fish Preservation) College of Fisheries, University of the Philippines, 1965
Keywords: Fish preservation